ANALISIS KEAKURASIAN INFUSION PUMP DENGAN TINGKAT KOMPONEN DALAM NEGERI (TKDN) MENGGUNAKAN METODE UNCERTAINTY - Dedy Iskandar; Eka Nuryanto Budisusila (LPPM POLBITRADA, 2025)
Component-Level Domestic Content Policy (TKDN) encourages the utilization of domestically produced medical devices; however, their accuracy and safety must be proven. This study aims to analyze the accuracy of domestic infusion pumps using the uncertainty measurement method. A total of four units from four brands (Endo, ESA Tech, Inmedik, and Krisma Care) were tested on the flow rate parameter with variations of 10, 50, 100, 200, and 300 mL/hour. Each test point was measured six times using a calibrated Fluke IDA 5 Infusion Device Analyzer. Data were analyzed through calculations of mean, correction, standard deviation, and expanded uncertainty (k = 2). Based on the analysis results, all TKDN infusion pumps (100%) met the tolerance limit of ±10% in accordance with the PO.002-18 standard and were declared fit for use. The highest correction value of 25.57 mL/hour (8.5%) was recorded for the Endo brand at a setting of 300 mL/hour, while the lowest correction of 0.21 mL/hour (0.7%) was found in ESA Tech. All measurement points across the four brands showed consistency within the permitted tolerance limits, with measurement uncertainty variations between ±0.15 and ±0.17 mL/hour. These findings prove that domestically produced infusion pumps possess accuracy and reliability equivalent to the standards required for clinical use.